The High Short Vowels in the Šakiai Dialect - Bacevičiūtė, Rima (Kalbotyra, 2004)
The article examines some of the vocalism features of the dialect Šakiai West-Aukštaitian dialect (the region of Kaunas). The quality, features of usage of the short vowels [i], [u] were subjected to experimental analysis. The phonological interpretation is the following: 1. Vowels of two kinds of quality were determined in the dialect: more open [i̲], [u̲] and more closed [i], [u]. 2. In word-internal position, the vowels [i̲] and [i], [u̲] and [u] are in clear complementary distribution, and they function as the allophones of the same phonemes. 3. In word-final position, an unsystematic phonological contrast between these vowels may sometimes be observed, so they should be viewed as separate phonemes. 4. The first components of acute diphthongs [i], [u] are mostly half-long and very open in the dialect.